2015
DOI: 10.1016/j.aquaculture.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Environmental performance of brackish water polyculture system from a life cycle perspective: A Filipino case study

Abstract: Life Cycle Assessment (LCA) was applied to assess the environmental performance of brackish water polyculture of black tiger prawn, mud crabs, tilapia and milkfish in a pond aquaculture system. The study was conducted on 15 production sites, located in Pampanga Province of the Philippines. The scope of analysis covered the hatchery or capture of juveniles from the wild up to the delivery of products to auction markets. Impact categories included eutrophication, acidification, climate change, land occupation, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…It considers variability in practices and environmental performances in aquaculture systems (Aubin et al . ). Social implications of aquaculture systems were studied using social LCA (Mathé ) and innovation capacity analysis (results not shown).…”
Section: Methodsmentioning
confidence: 97%
“…It considers variability in practices and environmental performances in aquaculture systems (Aubin et al . ). Social implications of aquaculture systems were studied using social LCA (Mathé ) and innovation capacity analysis (results not shown).…”
Section: Methodsmentioning
confidence: 97%
“…LCA is a methodology developed by the International Organization for Standardization ISO (2006a,b) to estimate the environmental impacts and identify processes that are less efficient from the environmental point of view. It was developed by the industrial sector, and since the year 2000, several LCA studies related to aquaculture species and rearing systems have been published (Pelletier & Tyedmers 2010;Cao et al 2011;Jerbi et al 2012;Huysveld et al 2013;Aubin et al 2015;Medeiros et al 2017). This methodology is divided into four major steps: goal and scope, inventory, impact assessment and interpretation of results.…”
Section: Environmental Impact Assessment Methodologiesmentioning
confidence: 99%
“…; Aubin et al . ). In contrast, other studies showed polyculture systems to have lower environmental impacts thanks to their potential for species complementarity (Kluts et al .…”
Section: Comparative Performances Of Aquaculture Systemsmentioning
confidence: 97%